A Study Of Mthfr Gene Polymorphisms In Patients With Nonsyndromic Orofacial Clefts And Their Parents [R5-130.5]. - Pal, Sumita (2009)
Tesis ini menggambarkan perkaitan antara polimorfisme nukleotida tunggal (SNP} gen MTHFR 677C→T dan 1298A→C dengan rekahan orofacial dalam populasi Malayu.